Quantification of Andrographolide Isolated from Andrographis paniculata Nees Obtained from Traditional Market in Yogyakarta Using Validated HPLC - Yandi Syukri; Ronny Martien; Endang Lukitaningsih; Agung Endro Nugroho (Universitas Gadjah Mada, 2016)
This research was aimed to quantification of andrographolide isolated from A. paniculata Ness found in traditional market in Yogyakarta using validated HPLC to obtain high level content of andrographolide. The extraction of andrographolide from A. paniculata was carried out using ethanol as the solvent. Fractionation and isolation were continued using a non-polar solvent. Next, the extracts were re-crystallized to obtain isolated andrographolide. The identity of the compound was confirmed through an analysis of the melting point, IR spectra, and TLC. The purity of the compound was confirmed by the validated HPLC. The data obtained were then compared using an analytical grade of andrographolide as the standard. The isolated andrographolide confirmed melting point, IR spectra and TLC analysis were similar to the standard andrographolide. The method to determine the content of isolated andrographolide showed an adequate precision, with a relative standard deviation (RSD) smaller than 1%. The accuracy showed good recovery values were obtained for all concentrations used. The HPLC method in this study showed specificity and selectivity with linearity in the working range and good precision and accuracy, making it very suitable for the quantification of andrographolide isolated in A. paniculata. When compared to the standard, the purity of the isolated andrographolide was 95.74 ± 0.29%.